An open labelled randomized clinical trial of fluoxetine versus dapoxetine treatment among men with premature ejaculation and its effect on marital satisfaction - Che' Man, Mohamad; Mohd Zain, Faridah; Yaacob, Najib Majdi; Ismail, Shaiful Bahari (2016)
Premature ejaculation (PE) reduces sexual satisfaction and quality of life. Both SSRI Fluoxetine and Dapoxetine have been used in the treatment of PE. Fluoxetine is used as off-label treatment meanwhile Dapoxetine is the first SSRI specifically designed for PE with short half-life and few side effects.